Digital Entrepreneurship on Purchase Decisions: Analysis of Content-Based Business, Online Store, and Business Matchmaking - Mulyana, Mumuh; Rainanto, Bambang Hengky; Sulistiono, Sulistiono; Fadillah, Adil; Said, Jamaliah (School of Business, IPB University (SB-IPB), 2025)
Backgrounds: The advancement of technology has significantly impacted various sectors, including food and beverage (F&B) companies. Previously, trading, shopping, and promotion activities were conducted directly, but now these activities are primarily online. Consequently, F&B owners need distinctive characteristics and effective use of digital media to stay competitive.Purpose: This study aims to determine the influence of digital entrepreneurship on purchase decisions within F&B companies in West Java, Indonesia.Design/methodology/approach: A quantitative research method was employed, surveying 100 respondents from F&B consumers using purposive sampling. Data were collected through a structured questionnaire and analyzed with Structural Equation Modeling (SEM) using SmartPLS v.4.0, including validity and reliability tests.Findings/Results: The study found a significant impact of digital entrepreneurship on purchase decisions. Positive influences were noted in content-based business, community-based business, matchmaking business, and promotion. However, the online store variable showed a positive but statistically insignificant effect.Conclusion: The results underscore the importance for F&B proprietors to strategically integrate digital entrepreneurship elements to enhance and optimize purchase decision dynamics.Originality/value (State of the art): This research highlights the growing significance of digital entrepreneurship in the F&B sector, offering insights into how various digital strategies influence consumer purchasing behavior, which is crucial for adapting to the evolving market landscape. Keywords: digital entrepreneurship, social media, digital marketing strategies, promotional content, purchase decisions.